A diachronic study on the treatment of culture-bound words in Chinese-English Dictionaries (1819–2014): A case study of confucian terms - Jinyan Li (Heliyon)
Cultural information has long been recognised as an integral part of bilingual dictionaries. However, previous studies have generally exhibited an insufficient treatment of cultural information, particularly of culture-bound words. As the cornerstone of traditional Chinese culture, Confucianism has contributed significantly to the formation of the Chinese mind and character. Accordingly, the representation of Confucianism in bilingual dictionaries is of great value for cultural dissemination and Chinese-language acquisition. Thus, the present study investigates how key Confucian terms are presented in three Chinese-English dictionaries: Wuche Yunfu (Morrison 1819), A Chinese-English Dictionary (Giles 1912) and New Age Chinese-English Dictionary (Pan 2014). The purpose of this study is threefold: i) to understand the lexicographic practice of Chinese-English dictionaries in their treatment of culture-bound words (Confucian terms); ii) to explore the diachronic changes in bilingual dictionaries at the macrostructural and microstructural levels; and iii) to investigate the user-friendly features of bilingual dictionaries. The study's findings shed light on the presentation of cultural information in Chinese-English dictionaries, which could help non-native users improve their learning of Chinese language and culture.